One more opportunity - Alarcón Gutiérrez, Christian Giusseppe (2017)
Sr. Editor In September 2011, the Canadian Society of Obstetrics and Gynecology recommended discussing with patients the benefit of bilateral salpinguectomy at the time of hysterectomy and in patients requesting irreversible contraception (1), and in November 2013 the Society American Oncology Gynecology recommended bilateral salpinguectomy systematically in benign hysterectomy and instead of tubal ligation. In addition, he introduced the concept of 'opportunistic' salpinguectomy, that is, considering it at the time of another pelvic surgery in patients over 35 years of age with parity fulfilled (2). However, there is insufficient evidence to recommend that a patient enter the operating room solely and exclusively for elective salpinguectomy, without further indication.